Abortion in Turkey: a matter of state, family or individual decision - (:unkn) unknown (My University, 1996)
This paper gives a historical, international and cultural outlook on the debate related to the 1982 legalization of abortion in the modern democratic republic of Turkey. A belief that the country is under-populated and subsequent pro-natalist concerns of the turn of the century seem to have strongly influenced the legal prohibition of abortion. The paper first discusses the widespread social practice and the permissive attitudes towards abortion in the late Ottoman Empire and in contemporary Turkey. The contrast between the above social situation and until recently the strict, non-permissive religious and secular attitudes are presented with a discussion of the effects of the westernization and secularization processes in the late Ottoman Empire. Moral concerns and judgements regarding abortion seem to have penetrated Ottoman society as part of the above processes beginning in the nineteenth century. The present day official religious interpretations seem to conform with the more conservative Islamic schools of thought rather than the more liberal Islamic interpretations. Furthermore, the 1982 laws which legalize abortion until the eight week of pregnancy consider family planning to be a family issue and bring the restriction of making married women have their husband's permission before preceding with abortion. As such, the present legal platform opens to question the rationales and population control motives behind the law and the importance of who it is that can make the decision to proceed with abortion. Thus, in the last 70 years a historical and ideological progression can be discerned in the line of assuming first the state and then the family to have decision making legitimacy as regards reproductive choices. Today, the platform of radical discussion has shifted to evaluating the importance of individual women in making this reproductive choice. In this context, in conclusion, the paper discussed the rationale and the logic behind and the implications for gender power structures of the existing legal situation in Turkey.
Keywords: Female; Humans; Pregnancy; Forecasting; Turkey; Health Knowledge, Attitudes, Practice; Cross-Cultural Comparison; Infant, Newborn; Decision Making; Abortion, Legal; Morals; Politics; Population Control; Women's Rights